PERTANGGUNGJAWABAN PIDANA DAN HUKUM ISLAM BAGI SIPIR YANG MENGEDARKAN NARKOTIKA DI LINGKUNGAN LEMBAGA PEMASYARAKATAN MENURUT PERATURAN MENTERI HUKUM DAN HAK ASASI MANUSIA NOMOR M. HH.16. KP. 05. 02 TAHUN 2011 TENTANG KODE ETIK PEGAWAI PEMASYARAKATAN - Safriadi, Safriadi; Nurdin, Ridwan (Universitas Islam Negeri Ar-Raniry, 2020)
trafficking of narcotics in Indonesia has penetrated into various living environments such as the work environment. One of them is a Penitentiary. For example, Warden in Jambi Class II A Penitentiary and in Sekayu Penitentiary as well as in several other Correctional Institutions have circulated and smuggled narcotics into Correctional Institutions which causes regulations of the Minister of Law and Human Rights Number M. HH.16. KP. 05. 02 of 2011 Regarding Penitentiary Employee Code of Ethics is not implemented to the maximum. The research question in this thesis is what is the legal responsibility for the warden who conducts narcotics distribution, what are the factors causing narcotics circulation by the warden and how is the view of Islamic criminal law towards the warden who circulates narcotics in prison. In this study the authors used a normative juridical research method that is based on legislation and relevant books. Form of legal liability for Warden who circulates narcotics in LP according to public view as a full responsibility including medeplager (participating) category, according to Law Number 35 of 2009 concerning Narcotics forms of responsibility in the form of criminal threats (death sentence, life sentence, imprisonment) and fines. According to the Regulation of the Minister of Law and Human Rights Number M. HH.16. KP. 05. 02 of 2011 concerning the Penitentiary Employee Code of Ethics is subject to administrative sanctions (terminated) if there is a decision of gingkah. Factors causing the Warden to circulate narcotics in Corrections Institutions are economic factors, the low mentality of the Warden involved, oversight in prison is weak, the number of narcotics addicts who are only in prison without rehabilitation. According to the Islamic Criminal Law the Warden who circulates narcotics in a Penal Institution is liable to a sanction in the form of rahmah ta'Ä«r (bodily punishment, independence, and a fine).Â